TINGKAT KEPERCAYAAN DAN MINAT BELI MASYARAKAT BANJARMASIN TERHADAP PRODUK HIJAU BERDASARKAN SEGMENTASI DEMOGRAFIS - Rizka Zulfikar; Prihatini Ade Mayvita (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
This study aims to assess the level of trust and intention in  Banjarmasin’s public purchasing towards green products based on demographic variables such as gender, age, income, occupation, education and its influence on the level of trust and intention in public purchasing. This study is a survey research using questionnaires as an instrument. Population and sample used in this study is the community of Banjarmasin and taken as many as 150 respondents using non-purposive sampling method. The analysis technique used is (1) descriptive analysis of qualitative - quantitative and comparative analysis of the average using SPSS software; (2) the influence and correlation test was analyzed with SEM using IBM AMOS Software Version 22. The study found that: (1) the level of confidence and interest in people's purchasing Banjarmasin city is good enough for assessment respondents in a category; (2) The demographic segments of potential that can be used as a target market of green products : female, age 31-40 years, self-employed, earning between Rp 5 million - Rp 9,999 million and education level S-1 and S-3 (3) Segmentation demographic does not have a significant influence on the level of trust and intention in buying community towards green products because of the results of the SEM analysis for demoraphics CR value does not exceed 1.96 and the Sig. value is greater than 0.05 (4) demographic segmentation based on the type of work and level of education has a significant correlation only with trust variabels, but do not have a significant correlation with green purchase intention variabels. Keywords :   Trust, purchase intention, green products, demographic segmentation